Nitrous Oxide Emissions and Carbon Sequestration in Turfgrass: Effects of Irrigation and Nitrogen Fertilization (Year 2) - R. Braun; D. Bremer (Kansas Agricultural Experiment Station Research Reports, 2017)
This study was conducted from 2013–2016 to determine how irrigation and N fertilization may be managed to reduce N2O emissions and enhance carbon sequestration. In this study, annual nitrous oxide (N2O) emissions were greatest in urea and the least in unfertilized (no N) among treatments. During summer, the lower irrigation treatment resulted in less N2O emitted. All fertilizer and irrigation treatments maintained acceptable quality and high levels of percent green cover; however, the controlled-release fertilizer resulted in more consistent turf quality and green cover compared to urea and unfertilized. Urea fertilizer had higher peak fluxes after fertilization and overall annual emissions than polymer-coated nitrogen (N) fertilizer. Thus, controlled-release N fertilizers, such as polymer-coated urea, and/or lower irrigation may reduce N2O emissions in turfgrass.
Keywords: trace gas; climate change; greenhouse gas